2006
DOI: 10.1111/j.1365-2249.2006.03023.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and secretion of interleukin-6 in human parvovirus B19 non-structural protein (NS1) transfected COS-7 epithelial cells

Abstract: SummaryHuman parvovirus B19 (B19) has been associated with a variety of autoimmune diseases, including rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). We have demonstrated previously that B19 non-structural protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 28 publications
(40 reference statements)
4
32
0
Order By: Relevance
“…Among the SLE patients with dilated cardiomyopathies, considerably raised levels of Th17-related cytokines were also observed in those with PVB19-NS1 antibody versus those without PVB19-NS1 antibody. These results were in agreement with the findings of previous studies demonstrating that PVB19 NS1 protein is a transactivator of IL-6 expression [99,100], indicating that NS1 may be important in the PVB19-related diseases.…”
Section: Systemic Lupus Erythematosus (Sle)supporting
confidence: 95%
“…Among the SLE patients with dilated cardiomyopathies, considerably raised levels of Th17-related cytokines were also observed in those with PVB19-NS1 antibody versus those without PVB19-NS1 antibody. These results were in agreement with the findings of previous studies demonstrating that PVB19 NS1 protein is a transactivator of IL-6 expression [99,100], indicating that NS1 may be important in the PVB19-related diseases.…”
Section: Systemic Lupus Erythematosus (Sle)supporting
confidence: 95%
“…Previous experiments using GFP to visualize NS1 PVB19 transfection in epithelial cells found an enhanced inflammatory response with a high expression and secretion of IL-6 [9]. Thus, NS1 PVB19 inflammatory signaling modulation activates signal transducers and activators of transcription 3 (STAT3) [10], which induce an enhanced ICAM1 expression [18].…”
Section: Discussionmentioning
confidence: 98%
“…It is shown that B19V proteins NS1 (Hsu et al , 2006; Kerr et al , 2001) and VP1u (Tzang et al , 2009a) induce IL-6 mRNA expression. B19V proteins during viraemia could induce IL-6 production in RA patients.…”
Section: Discussionmentioning
confidence: 99%